Sistem Pakar Untuk Mengetahui Minat dan Bakat Pada Anak Berbasis Web Dengan Metode Forward Chaining - Made Risza Kartika; Yogo Dwi Prasetyo; Sena Wijayanto (STMIK Budi Darma, 2022)
In the era of the COVID-19 pandemic (Coronavirus Disease-19) it has affected various fields, especially the field of psychology in knowing children's interests and talents. Children's interests and talents are parents' problems in knowing the hidden abilities of children, especially at the age of 4-6 years. According to the journal US Office Of Education (USOE) America, the age of 4-6 years is a suitable age to find out interests and talents by conducting an aptitude interest test. The benefits of parents knowing the interests of children's talents, namely parents can find out the right and appropriate level of education. The results of the interview with Mrs. Rr.Wara Setija Brawidjajani.,S.Psi obtained information that interests and talents in children can be known by direct observation or direct observation of children's growth and development at home. The results of interviews with experts obtained data testing and training data. Therefore, the forward chaining method is used because of its compatibility with the method used by psychologists. The forward chaining method is a method that uses sustainable premises to find conclusions. Using this expert system can make it easier for every parent to find out their child's interests and talents as well as the right way of learning with an accuracy rate of 91.8%.